Harmonization of environmental legislation: world practice and major development trends (Journal of actual problems of jurisprudence, 2018)
The urgency of the problem is caused by the need to promote a favorable state of the environment, the meaningful use of natural resources, which depends on a number of factors. Therefore, the goal of the work is not only to study the environmental legislative framework, but also its interaction in different countries. A key approach to investigating this problem is to identify ways of harmonizing and interrelating environmental legislation in the world and in a single country. As such cooperation allows to take experience in developing countries, in more developed ones, in solving environmental issues, thereby maintaining the state of their state, and also reducing the accumulating influence on the world space.These are the issues that are considered in this paper. The article also analyzes the domestic legislation in the countries of Europe, America, and Asia and shows that the adoption of certain laws is carried out on the basis of existing ones. The materials of the work are of practical value for countries that begin their journey in the processes of enacting legislation in the field of ecology. Harmonization of such legislation is a necessary component for maintaining a stable development of the environment and preserving natural resources for future generations.Key words: harmonization of environmental legislation, convention, legislative activity, pollution of environment, international legal documents.